1997
DOI: 10.1038/sj.cdd.4400206
|View full text |Cite
|
Sign up to set email alerts
|

Flupirtine protects both neuronal cells and lymphocytes against induced apoptosis in vitro: Implications for treatment of AIDS patients

Abstract: In the present study we demonstrate that flupirtine, an already clinically used, centrally acting, non-opiate analgesic agent, protects rat cortical neurons against HIV-gp120 induced apoptotic cell death. The drug was active at concentrations between 1 and 10 mg/ml. Furthermore we show inhibition of in vitro induced apoptosis in human blood mononuclear cells, using flupirtine. Induced apoptosis in peripheral blood mononuclear cells from healthy individuals and HIV-1 infected patients was reduced to approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this regard, it has been demonstrated that morphine can activate the TNFα and IL-6 promoters through NF-κB (Roy et al 1998). Most often, opioids by themselves are not intrinsically toxic but significantly contribute in neuronal toxicity leading to neuronal injury (Muller et al 1997). Morphine and other opioids have been shown to induce oxidative stress (OS) in the immune system as well as in the central nervous systems, which leads to the induction of TNFα (Bhat et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been demonstrated that morphine can activate the TNFα and IL-6 promoters through NF-κB (Roy et al 1998). Most often, opioids by themselves are not intrinsically toxic but significantly contribute in neuronal toxicity leading to neuronal injury (Muller et al 1997). Morphine and other opioids have been shown to induce oxidative stress (OS) in the immune system as well as in the central nervous systems, which leads to the induction of TNFα (Bhat et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cells (0.5ϫ10 6 ) were cultured in 500 µl medium composed of MEM supplemented with 10 mM HEPES buffer, 2.6 % sodium bicarbonate, 0.1 U/ml penicillin, 0.1 U/ml streptomycin, 10 % FCS and 1 mM glutamine for 24 hours under 5 % CO 2 and 37°C [22].…”
Section: Patients and Methods S Blood Samplesmentioning
confidence: 99%